La deducción legal de los acervos y su incidencia en la Herencia Yacente, en la Unidad Judicial Civil del Cantón Riobamba, en el período enero- junio 2015. - Damián Gauño, Janneth Elizabeth (2016)
This research work is the study of the assets and the incidence that cause on the inheritance recumbent. The Civil Code has risen with the rules of the collections that allow these deductions to inheritance law. Civil Code, Article 1001.-in all succession by cause of death, to implement the provisions of the deceased or to the law, provisions will be deducted from the acquits or mass of assets left by the deceased, including hereditary claims. 1st.-The coasts of the publication of the testament so the attached to the opening of the succession, which is due by the last illness, and the funeral expenses; 2nd.-inherited debts; 3th.-The progressive tax that cause the undivided; and 4th.-the conjugal portion to any place in all orders of succession. On this preliminary step; after the deduction of the assets, it can divide the inheritance recumbent, which in simple terms is: between the opening of the succession, the acceptance and acquisition of inheritance by the successors half a period of time more or less long during which the legal relations undamaged of the inheritance are lacking. Which directly affects the heirs as universal, as well said the Civil Code, Art. 1125.-The assigns to universal title, and even if in the testament is qualify them of legatees, heirs and represent the person of the testator to succeed him in all his rights and transmissible obligations. The heirs are also liable to testamentary loads, it means, they constitute for the testament itself, and not imposed on certain people